a(bx+3)=cx-10

Simple and best practice solution for a(bx+3)=cx-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a(bx+3)=cx-10 equation:


Simplifying
a(bx + 3) = cx + -10

Reorder the terms:
a(3 + bx) = cx + -10
(3 * a + bx * a) = cx + -10
(3a + abx) = cx + -10

Reorder the terms:
3a + abx = -10 + cx

Solving
3a + abx = -10 + cx

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Reorder the terms:
10 + 3a + abx + -1cx = -10 + cx + 10 + -1cx

Reorder the terms:
10 + 3a + abx + -1cx = -10 + 10 + cx + -1cx

Combine like terms: -10 + 10 = 0
10 + 3a + abx + -1cx = 0 + cx + -1cx
10 + 3a + abx + -1cx = cx + -1cx

Combine like terms: cx + -1cx = 0
10 + 3a + abx + -1cx = 0

The solution to this equation could not be determined.

See similar equations:

| 3x(2x-5)(3x+1)=0 | | -15=-3+4u | | 15(5x-4)-(3x+1)=40x+3 | | 16=2w+2 | | 0.3x-7=15 | | 3(m-6)=10 | | 0.5x+9=30 | | 900=3x+300 | | ab+3b-2a-6= | | x=3x+2x+x+30 | | 2(x+4)=2x-4(x-3) | | 25=17+4x | | x=6x+30 | | 3z^2-23z-8= | | 6-(10x+2)=8+(2x-10) | | 5q=1+p | | 5p-2q=0 | | 3x^2-10x-100=0 | | x^3+x^2+4x+1=0 | | x^3-x^2+4x+1=0 | | 80*3=400 | | 3x^2-37x+48=0 | | 3a^3-2a^2+a= | | 4/4=4 | | x=5x+25 | | D^2-2D+7=0 | | -2x-4x+5=8 | | 7x-5=x+9 | | (x-2)180=900 | | 2x+.1875=y | | 4x-9x-6=12 | | 2x^2+4y+4=0 |

Equations solver categories